2022
DOI: 10.3390/polym14163233
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Alginate/Chitosan Scaffolds for Cardiac Tissue Engineering: The Influence of Its Three-Dimensional Material Preparation and the Use of Gold Nanoparticles

Abstract: Natural biopolymer scaffolds and conductive nanomaterials have been widely used in cardiac tissue engineering; however, there are still challenges in the scaffold fabrication, which include enhancing nutrient delivery, biocompatibility and properties that favor the growth, maturation and functionality of the generated tissue for therapeutic application. In the present work, different scaffolds prepared with sodium alginate and chitosan (alginate/chitosan) were fabricated with and without the addition of metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…The studied samples showed high values of porosity, (>90%), which coincides with the data presented in [40]. For samples treated with ultrasound, the porosity values did not differ significantly.…”
supporting
confidence: 90%
“…The studied samples showed high values of porosity, (>90%), which coincides with the data presented in [40]. For samples treated with ultrasound, the porosity values did not differ significantly.…”
supporting
confidence: 90%
“…They have been shown as promising nanomaterials for biomedical-related applications from imaging to diagnostics. 34,35 Several studies have explored the incorporation of GNP into scaffolds, including alginate-chitosan, 36 poly (e-caprolactone), 37 gelatin methacrylate (GelMA) UV-crosslinked hydrogel layer of cardiac tissue patch, 38 and decellularized omental matrix. 39 These studies have demonstrated significantly enhanced cell adhesion, proliferation, and viability.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have seen an increased interest in alginate/chitosan systems due to their emerging applications in various areas, including the pharmaceutical and food industries for the encapsulation and controlled release of biologically active substances [ 11 ], in medicine for tissue engineering [ 12 , 13 , 14 , 15 ], and in the environmental sciences for waste-water remediation [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%